2020
DOI: 10.1111/cei.13442
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus ORCA-010 increases the type 1 T cell stimulatory capacity of melanoma-conditioned dendritic cells

Abstract: Summary Immune checkpoint blockade has resulted in durable responses in patients with metastatic melanoma, but only in a fraction of treated patients. For immune checkpoint inhibitors (ICI) to be effective, sufficient infiltration with tumor‐reactive T cells is essential. Oncolytic viruses (OV) selectively replicate in and lyse tumor cells and so induce an immunogenic form of cell death, providing at once a source of tumor‐associated (neo)antigens and of danger signals that together induce effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Although great progress in tumor treatment was achieved by using oncolytic adenoviruses [ 3 , 53 , 54 ], how to improve their therapeutic effects as a carrier of genes remains a clinically relevant question. Additionally, the heterogeneity of oncolytic adenoviruses may induce an inflammatory response, triggering an antiviral response of the immune system and reducing their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Although great progress in tumor treatment was achieved by using oncolytic adenoviruses [ 3 , 53 , 54 ], how to improve their therapeutic effects as a carrier of genes remains a clinically relevant question. Additionally, the heterogeneity of oncolytic adenoviruses may induce an inflammatory response, triggering an antiviral response of the immune system and reducing their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…ORCA-010 is also a modified HAdV-C5, carrying RGB transgene and 24 bp deletion. The vector has an additional mutation in the E3 gene in the sequence encoding 19K protein [ 134 ]. Phase I clinical trials showed a good safety profile.…”
Section: Oncolytic Adenoviruses: Clinical Progressmentioning
confidence: 99%
“…In addition, melanoma promotes the switch of myeloid cells through immuno-suppressive macrophage-like cells rather than DCs [ 166 ]. The use of oncolytic virus (i.e., ORCA-010) could stimulate a specific differentiation of DCs and T cell priming by producing tumor-associated neo-antigen in order to increase the response to ICIs [ 167 ]. The therapeutic potential of DC vaccines was, recently, supported in an interesting preclinical work by Zhou and collaborators.…”
Section: Tme Implications In Drug Resistance For Melanomamentioning
confidence: 99%